2004
DOI: 10.1017/s1481803500009416
|View full text |Cite
|
Sign up to set email alerts
|

Laryngoscopic views during rapid sequence intubation in the emergency department

Abstract: Objectives: Our objective was to document and compare the views obtained at laryngoscopy during emergency department (ED) rapid sequence intubation (RSI) by anesthetists and emergency physicians of varying seniority and experience. Methods: Data were prospectively collected on every intubation attempt in 7 urban Scottish EDs for 2 calendar years, commencing Jan. 11, 1999. Data included patient's age, gender, grade and specialty of intubator, laryngoscopic grade, and number of intubation attempts. Quality of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…In a multicenter analysis including over 6,000 ETIs, the first attempt success rates varied by provider experience with the first year emergency medicine residents having success rate of only 72% compared to 82% and 88% in the second year and third year, respectively [ 17 ]. First attempt success also decreases with Cormack-Lehane view where grade 3 views have first attempt success rates near 40%, similar to those noted in our study [ 16 ]. Complications occur more frequently in cases where multiple ETI attempts are made [ 3 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a multicenter analysis including over 6,000 ETIs, the first attempt success rates varied by provider experience with the first year emergency medicine residents having success rate of only 72% compared to 82% and 88% in the second year and third year, respectively [ 17 ]. First attempt success also decreases with Cormack-Lehane view where grade 3 views have first attempt success rates near 40%, similar to those noted in our study [ 16 ]. Complications occur more frequently in cases where multiple ETI attempts are made [ 3 ].…”
Section: Discussionsupporting
confidence: 90%
“…We felt a difficult airway (Cormack-Lehane grade 3) would allow for greater discrimination between the movement patterns of novice and experienced providers. As Cormack-Lehane grade 3 views are infrequently encountered in emergency airway management, we focused our efforts on the cadaver model [ 14 16 ]. Also, from a patient safety and research ethics standpoints, we did not feel it was in patients' best interest to perform multiple intubation attempts on a patient or patients with a difficult airway, especially with novice providers, for a proof of concept study.…”
Section: Limitationsmentioning
confidence: 99%
“…[17][18][19] It is clear from our results that the intubation is most likely to be successful on the first attempt regardless of specialty, and successful intubation on the first attempt should be the aim of every ED intubation attempt.…”
Section: Discussionmentioning
confidence: 70%
“…Graham et al also reported that anesthetic trainees obtained better laryngoscopic views than Emergency Medicine trainees, but these differences disappeared with increasing Emergency Physician seniority (19). Furthermore, Kelly et al suggested that the seniority of Emergency Physicians likely reduced the rate of unscheduled return visits (6).…”
Section: Discussionmentioning
confidence: 99%